2013
DOI: 10.1007/s00534-013-0616-0
|View full text |Cite
|
Sign up to set email alerts
|

Role of adjuvant surgery for patients with initially unresectable pancreatic cancer with a long‐term favorable response to non‐surgical anti‐cancer treatments: results of a project study for pancreatic surgery by the Japanese Society of Hepato‐Biliary‐Pancreatic Surgery

Abstract: Purpose A multicenter survey was conducted to explore the role of adjuvant surgery for initially unresectable pancreatic cancer with a long-term favorable response to nonsurgical cancer treatments. Methods Clinical data including overall survival were retrospectively compared between 58 initially unresectable pancreatic cancer patients who underwent adjuvant surgery with a favorable response to non-surgical cancer treatments over 6 months after the initial treatment and 101 patients who did not undergo adjuvan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
140
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 178 publications
(147 citation statements)
references
References 30 publications
4
140
3
Order By: Relevance
“…A study by Satoi et al compared a group that underwent CS following primary treatment for LURPC to a group that did not, and found that the median survival was significantly prolonged in the CS group (CS vs. non-CS: 39.7 vs. 20.8 months, respectively; P<0.001) (25). Similarly, Habermehl et al reported that median survival was significantly prolonged in the CS group (CS vs. non-CS: 11.9 vs. 14.4 months, respectively; P=0.004) (15); they also reported an even longer patient survival if the surgical margins were found to be clear (R0 vs. R1 vs. R2: 22.1 vs. 15.6 vs. 10.3 months, respectively) (15).…”
Section: Discussionmentioning
confidence: 99%
“…A study by Satoi et al compared a group that underwent CS following primary treatment for LURPC to a group that did not, and found that the median survival was significantly prolonged in the CS group (CS vs. non-CS: 39.7 vs. 20.8 months, respectively; P<0.001) (25). Similarly, Habermehl et al reported that median survival was significantly prolonged in the CS group (CS vs. non-CS: 11.9 vs. 14.4 months, respectively; P=0.004) (15); they also reported an even longer patient survival if the surgical margins were found to be clear (R0 vs. R1 vs. R2: 22.1 vs. 15.6 vs. 10.3 months, respectively) (15).…”
Section: Discussionmentioning
confidence: 99%
“…In spite of recent progress in treatment strategies, the current protocols of chemotherapy regimens remain insufficient to cure the patients (4,5). Recently, we and other groups have reported a new concept of "adjuvant surgery" in which PDAC patients are treated with preoperative chemotherapy, followed by surgical resection, which contributes to long-term survival for locally advanced cases (6,7).…”
Section: Introductionmentioning
confidence: 99%
“…Although there are no clear answers in relation to this situation, Satoi et al (10) received better response in patients who had at least 240 days that elapsed following the start of treatment in their sub-group analysis and this result was attributed to the better patient selection and the higher dose of chemotherapy received. We also performed a surgical procedure in our patient 10 months after the start of treatment and we obtained a survival of approximately 26 months.…”
Section: Discussionmentioning
confidence: 99%
“…The most updated publication on this topic was published by Satoi et al (10) Surgical treatment was performed on 58 patients responding to medical treatment over a period of more than 6 months among 150 non-resectable pancreatic cancer patients; the remaining 101 patients who did not undergo surgery were determined as the control group. Surgical mortality and morbidity values were found to be similar with those with resectable cancers (1.7%-47%).…”
Section: Discussionmentioning
confidence: 99%